EXPLANATION OF THE MUSICAL HERITAGE OF ROMANTICISM OF WESTERN EUROPE AT THE TURN OF THE 18-19 CENTURIES: IN THE PERSPECTIVE OF ART HISTORY ANALYSIS - Мельничук, Святослав (SWorldJournal, 2023)
The article considers the peculiarities of development of musical culture of the late 18TH - 19TH century. It is noted that the French revolution was the beginning of a transformation of society, had a stronger influence on the formation of a new world Ou